Atlantic crescent: building geographies of black and Muslim liberation in the African diaspora - Morgan, Alaina M. (The University of North Carolina Press, 2025)
Cover -- Half Title -- Title Page -- Dedication -- Contents -- List of Illustrations -- Introduction: The Serpent That Deceived the World -- Part I: Discourses -- Chapter One. Black Islam in a History of Overlapping Diasporas -- Chapter Two. The Atlantic Crescent from Lahore to Iowa -- Chapter Three. Muslims Speak to the Ummah in Black and White -- Interlude. Transitions, Crises, and Choices -- Part II: Translations -- Chapter Four. Bermuda Crescent: Black Muslim Resistance and Decolonization in Translation -- Chapter Five. The Bold Muslims We Were: Gender, Education, and Anticolonial Islam -- Chapter Six. Who You Gonna Call?: Islam, American Neo-Imperialism, and Dopebusting in the Inner City -- Epilogue. The Bow, the Arrow, and the Crescent: Blackness and Islam in the Past, Present, and Future -- Acknowledgments -- Notes -- Bibliography -- Index -- A -- B -- C -- D -- E -- F -- G -- H -- I -- J -- K -- L -- M -- N -- O -- P -- Q -- R -- S -- T -- U -- V -- W -- X -- Y -- Z.